2023
DOI: 10.1037/cps0000130
|View full text |Cite
|
Sign up to set email alerts
|

Personalizing youth psychotherapy: A scoping review of decision-making in modular treatments.

Abstract: Modular youth psychotherapies are increasingly popular, in part because their flexibility facilitates personalizing, but the clinician decision-making required can be complex. We investigated decision guidance in 20 modular youth psychotherapies, described in 67 articles identified via a systematic search. Decision guidance was limited. Clinical judgment was recommended in all therapies; 95% recommended using baseline assessment, 65% measurement-based care, and 25% prior research. Most commonly, guidance invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Specifically, when given a source and target topic expressed as two brief utterances, the target-oriented dialog (TOD) agent must generate a transitional response that connects the two topics seamlessly. Due to their purposeful and flexible nature, target-oriented dialog agents possess a wide range of applications, spanning conversational recommendation [13], psychotherapy [14], and education [15].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, when given a source and target topic expressed as two brief utterances, the target-oriented dialog (TOD) agent must generate a transitional response that connects the two topics seamlessly. Due to their purposeful and flexible nature, target-oriented dialog agents possess a wide range of applications, spanning conversational recommendation [13], psychotherapy [14], and education [15].…”
Section: Introductionmentioning
confidence: 99%
“…Unlike traditional evidence-based treatments (EBTs), where sessions may be outlined in the order in which they need to be implemented; modular approaches to therapy vary in degree of flexibility regarding order, duration, and which intervention elements to include in the treatment. Venturo-Conerly et al (2022) reviewed the literature on decision guidance in child modular therapies and found that decision-making support systems (DSSs) come in a spectrum of options from very flexible to very rigid. Some treatments provide flowcharts prescribing the order of elements, while others can be organized and delivered in any order based on the provider’s preference.…”
mentioning
confidence: 99%
“…In their article, Venturo-Conerly et al (2022) highlight that none of the youth modular interventions that they reviewed include the use of algorithms and statistical models as part of their DSS. Incorporating statistical models as part of DSSs is an exciting and potentially fruitful new area of research as the field continues to develop ways to improve youth outcomes.…”
mentioning
confidence: 99%
“…Because of their flexible nature, modular treatments require more clinician decision-making compared to more prescriptive approaches with a predetermined sequence of sessions. To distill the decision-making process in youth-specific modular psychotherapy treatments, Venturo-Conerly et al (2023) conducted a scoping review to identify the most common tools available for clinical decision-making. They found that clinical judgment based on detailed module descriptions is most commonly used, and that treatment protocols rarely suggest using client input or statistical models in decision-making.…”
mentioning
confidence: 99%